2013
DOI: 10.1016/j.jmbbm.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of mechanical anisotropy in brain tissue and implications for transversely isotropic material models of white matter

Abstract: White matter in the brain is structurally anisotropic, consisting largely of bundles of aligned, myelin-sheathed axonal fibers. White matter is believed to be mechanically anisotropic as well. Specifically, transverse isotropy is expected locally, with the plane of isotropy normal to the local mean fiber direction. Suitable material models involve strain energy density functions that depend on the I4 and I5 pseudo-invariants of the Cauchy–Green strain tensor to account for the effects of relatively stiff fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
183
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(198 citation statements)
references
References 64 publications
9
183
1
1
Order By: Relevance
“…In selected studies, the regional and local anisotropic variation in brain material properties was examined [76][77][78][79][80][81]. At small strains, the relative stiffness of highly oriented brain stem samples showed modest anisotropy [81].…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
See 1 more Smart Citation
“…In selected studies, the regional and local anisotropic variation in brain material properties was examined [76][77][78][79][80][81]. At small strains, the relative stiffness of highly oriented brain stem samples showed modest anisotropy [81].…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…In some cases, existing material models gleaned from the composite materials community can help assist in interpreting anisotropic material behavior [79,80]. Some models of the white matter already suggest how different cell types may couple to each other and propose how structural elements of the tissue interact in complex manner to expose a subpopulation of axons to high mechanical loading [86][87][88][89][90].…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…Indeed, soft biological tissue is proven to be represented well by the Ogden formulation and most of the mechanical test data available for brain tissue in the literature fits with an Ogden hyperelastic function. 5,10,16,35,36 Finally, the Ogden hyperelastic constants have been implemented into our FE model to indicate a very good consistency of constitutive modeling which originates from a fairly suitable assumption in the behavior of brain tissue with FE modeling outcomes ( Figure 3). The FE results for longitudinal ( Figure 3a) and circumferential ( Figure 3b) loading directions, interestingly, depicted fairly good agreement with the experimental results as there are 18.21% and 35.96% variation, respectively.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…In experimental studies, brain tissue has shown a nonlinear, viscoelastic, and anisotropic, mechanical behavior (Feng et al, 2013;Miller and Chinzei, 1997;Prevost et al, 2011). In addition, it is a highly compliant material, which makes its mechanical characterization a challenging task.…”
Section: Introductionmentioning
confidence: 99%